Baroda's experiment in urban decentralization : a study of some administrative aspects - Bhatt, Anil H., 1937- (Dept. of Political Science, Faculty of Arts, Maharaja Sayajirao University of Baroda : copies can be had of University Publications Sales Unit, 1978)
On the ward reorganization scheme of the Baroda Municipal Corporation.